文档介绍:7(x+2)—4(x—1)+2(3x—1)=27 15(4x—8)—5(2x+10)=6(5x—20)
x 7 8x 9x 3 4x 2x-x+3=-2x
x 3x
7(x+2)—4(x—1)+2(3x—1)=27 15(4x—8)—5(2x+10)=6(5x—20)
x 7 8x 9x 3 4x 2x-x+3=-2x
x 3x 5x
3x 7 4x 6x 2 3(x 2) 1 x (2x 1)
5(x 2) 2(5x 1) 2(x 1) (x 2) 3(4 x)
4x+3=2(x-1)+6 (x+1)-2(x-1)=7-3x
1-2(2x+3)=3(2x-5) (x+1)-2(x-1)=4-3x
4x 3(20 x) 6x 7(9 x) 4x 2(x 2) 12 (x 4)
4(x-2)-3(4x-1)=9(1-x)
2(x4)2x7(x1)
2x (5x 16) 3 2(3x 4) 4x 3(20 x) 6x 7(9 x)
1 1
2{3[4(5x 1) 8] 20} 7 1 6( x 4) 2x 7 ( x 1)
2 3
2(y+2)-3(4y-1)=19(1-y)
1x
1(32x)1
5
2
2(x-2)-6(4x-1)=2(1-x) 7(x-2)-3(5x-1)=9(1-x)
3(20-y)=6y-4(y-11) 15-(8-5x)=7x+(14-3x)